Tungiasis: A Rare Parasitic Infestation in Genitals of a Native Male from Kathmandu - Shrivastav, Shreya; Adhikari, Ram Chandra (Journal of Nepal Health Research Council, 2018)
Tungiasis is a common parasitic infection inmany parts of the world, including South and Central America and parts of Africa. It is rare in other places, such as in India and Pakistan and imported cases have been reported in Taiwan, Italy, the United States of America, etc. Our diagnosis was made based on histopathologiocal features of the parasite, which corresponds too ther reports and description of tungiasis.1-3 It was treated by surgical excision alone. The fact that the disease has never been reported in Nepal makes it difficult to diagnose clinically, but should be considered in the future. Histopathology can aid in diagnosingthis rare condition. Keywords: Nepal; tunga penetrans; tungiasis.